2017
DOI: 10.3892/etm.2017.5590
|View full text |Cite
|
Sign up to set email alerts
|

Metoprolol protects cardiomyocytes in rabbit model of heart failure by regulating Cx43

Abstract: This study investigated the protective effect of metoprolol on cardiomyocytes in rabbits with heart failure and its possible mechanism. Sixty New Zealand white rabbits were randomly divided into infarction group and non-infarction group, 30 in each group. Myocardial infarction was constructed by ligation of anterior descending branch of coronary artery. Coronary artery threading without ligation after thoracotomy was performed for rabbits in non-infarction group. After model construction, rabbits in each group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This pathway can recover gap junction communication, leading to improved conduction velocity. These changes ultimately reduce susceptibility to ventricular arrhythmias ( Zhou et al., 2017 ; Zhai et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This pathway can recover gap junction communication, leading to improved conduction velocity. These changes ultimately reduce susceptibility to ventricular arrhythmias ( Zhou et al., 2017 ; Zhai et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…reduced or eliminated in the infarct zone and border zone after acute focal ischemia (14,15), and this effect is accompanied by Cx43 redistribution, which undermines the conduction velocity and the inhomogeneous anisotropy of cardiac conduction, causing severe ventricular arrhythmias (16,17). Cx43 remodeling plays a significant role in the pathogenesis and prognosis of ischemic arrhythmias, and interventions targeting Cx43 remodeling may reduce the occurrence of ventricular arrhythmias after MI.…”
Section: Discussionmentioning
confidence: 99%
“…According to the theory of miRNA biology, miR‐1 may down‐regulate Cx43 by forming the RNA‐induced silencing complex. Several researches have reported that metoprolol improved Cx43 expression and changed its distribution . Jiang et al .…”
Section: Discussionmentioning
confidence: 99%
“…indicated that metoprolol was effective in reducing ventricular arrhythmias by lighting the decreased expression of Cx43 induced by MI. Similarly, Zhai et al . found that metoprolol can protect cardiomyocytes in the heart failure model, and the mechanism was possibly related to the up‐regulation of Cx43 in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation